Baler - Iglesias, Roy
"Baler is a love story between Feliza, the daughter of a rebel commander and Celso, a half-Spanish soldier, set during the twilight years of the Spanish regime in the Philippines. The young couple struggle to keep their forbidden love alive despite familial and political tensions, culminating in an almost year-long blockade known as the Siege of Baler."